Emergence of carbapenem resistance in persistent Shewanella algae bacteremia: the role of pdsS G547W mutation in adaptive subpopulation dynamics - Yao-Ting Huang; Po-Yu Liu (BMC, 2024)
Abstract This study elucidates the in vivo genetic mechanisms contributing to the emerging resistance to carbapenem in Shewanella algae through a lens of adaptive microbial evolution. Leveraging PacBio amplification-free sequencing, we tracked the evolution of β-lactam resistance in clinical isolates from a persistent S. algae bacteremia case amidst antimicrobial therapy. Our investigation spotlighted a recurrent G547W mutation in the sensor histidine kinase (pdsS), which was associated with the overexpression of an OmpA-like protein (pdsO) within a proteobacteria-specific sortase system. Intriguingly, we observed a recurrent switch between wild-type and G547W alleles, revealing an adaptive expansion and contraction of underlying cell subpopulations in response to β-lactam exposure. Comparative transcriptome analyses further demonstrated the overexpression of genes pivotal for membrane integrity, biofilm formation, immune evasion, and β-lactamase activation in resistant samples. This underscores the pre-existence of resistant cells at minuscule frequencies even without antibiotic pressure, potentially explaining the within-host emergence of resistance during antibiotic treatments. Our findings provide pivotal insights into the dynamic genetic adaptations of S. algae under therapeutic pressures, unmasking intricate resistance mechanisms and highlighting the critical role of subpopulation dynamics in treatment outcomes.